Influence of epoxy, polytetrafluoroethylene (PTFE) and rhodium surface coatings on surface roughness, nano-mechanical properties and biofilm adhesion of nickel titanium (Ni-Ti) archwires. (14th February 2018) - Asiry, Moshabab A; AlShahrani, Ibrahim; Almoammar, Salem; Durgesh, Bangalore H; Al Kheraif, Abdulaziz A; Hashem, Mohamed I
Abstract: Aim. To investigate the effect of epoxy, polytetrafluoroethylene (PTFE) and rhodium surface coatings on surface roughness, nano-mechanical properties and biofilm adhesion of nickel titanium (Ni-Ti) archwires Methods. Three different coated (Epoxy, polytetrafluoroethylene (PTFE) and rhodium) and one uncoated Ni-Ti archwires were evaluated in the present study. Surface roughness (Ra) was assessed using a non-contact surface profilometer. The mechanical properties (nano-hardness and elastic modulus) were measured using a nanoindenter. Bacterial adhesion assays were performed using Streptococcus mutans (MS) and streptococcus sobrinus (SS) in an in-vitro set up. The data obtained were analyzed using analyses of variance, Tukey's post hoc test and Pearson's correlation coefficient test. Result. The highest Ra values (1.29 ± 0.49) were obtained for epoxy coated wires and lowest Ra values (0.29 ± 0.16) were obtained for the uncoated wires. No significant differences in the Ra values were observed between the rhodium coated and uncoated archwires ( P  > 0.05). The highest nano-hardness (3.72 ± 0.24) and elastic modulus values (61.15 ± 2.59) were obtained for uncoated archwires and the lowest nano-hardness (0.18 ± 0.10) and elastic modulus values (4.84 ± 0.65) were observed for epoxy coated archwires. No significant differences in nano-hardness and elastic modulus values were observed between the coated archwires ( P  > 0.05). The adhesion of Streptococcus mutans (MS) to the wires was significantly greater than that of streptococcus sobrinus (S S). The epoxy coated wires demonstrated an increased adhesion of MS and SS and the uncoated wires demonstrated decreased biofilm adhesion. The Spearman correlation test showed that MS and SS adhesion was positively correlated with the surface roughness of the wires. Conclusion. The different surface coatings significantly influence the roughness, nano-mechanical properties and biofilm adhesion parameters of the archwires. The evaluated parameters were most influenced by epoxy coating followed by PTFE and rhodium coating. A positive correlation was detected between surface roughness and biofilm adhesion.